2017
DOI: 10.1590/s1517-707620170004.0236
|View full text |Cite
|
Sign up to set email alerts
|

Membranas de polihidroxibutirato com hidroxiapatita para utilização como biomaterial

Abstract: RESUMOO avanço da tecnologia dos biomateriais permite desenvolver materiais que auxiliam nos processos reconstrutivos de partes do corpo e incrementam tratamentos e melhora a qualidade de vida dos seres humanos. O Polihidroxibutirato (PHB) é um polímero biocompatível, biodegradável, muito estudado para aplicações médicas e suas propriedades ainda podem ser adequadas para outras diversas aplicações com a incorporação da hidroxiapatita (HA). Esta é uma carga inorgânica biocompatível e bioativa já presente nos te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 16 publications
2
4
0
4
Order By: Relevance
“…Oliveira et al [54], when synthesized the hydroxyapatite via wet reaction, observed a morphology of the powder with a porous structure and with varied pore size, as well as observed in the present study. According to [42,49], the presence of pores smaller than 30 μm should be highlighted because they allow better neovascularization and growth of fibroblasts inside the supports, when these are applied as biomaterials. Corroborating also with the studies of [41] which synthesized HAp using 800 °C as decomposition temperature, it was verified that the particles were agglomerated and had almost spherical morphology.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oliveira et al [54], when synthesized the hydroxyapatite via wet reaction, observed a morphology of the powder with a porous structure and with varied pore size, as well as observed in the present study. According to [42,49], the presence of pores smaller than 30 μm should be highlighted because they allow better neovascularization and growth of fibroblasts inside the supports, when these are applied as biomaterials. Corroborating also with the studies of [41] which synthesized HAp using 800 °C as decomposition temperature, it was verified that the particles were agglomerated and had almost spherical morphology.…”
Section: Resultsmentioning
confidence: 99%
“…This way it allows the control of synthesis, which involves reactions between calcium and phosphorus precursors, through the control of temperature and pH of the solution [30,[37][38][39][40]. The calcium precursor commonly used to obtain hydroxyapatite is calcium hydroxide from synthetic origin or biological origin such as sea shell and eggshell [8,[41][42][43][44][45][46][47]. The use of eggshell is suggested as an alternative for solid waste assessment; it represents 10% of the weight of the egg, generating a waste quantity of 5.92 million tons per year worldwide [48,49].…”
Section: Introductionmentioning
confidence: 99%
“…Dentre os biopolímeros, um que vem se destacando é o Poli (βhidroxibutirato) (PHB). O PHB é um polímero biocompatível, biodegradável, muito estudado para aplicações médicas e suas propriedades ainda podem ser adequadas para outras diversas aplicações (HUANG;SHETTY;WANG, 1990;SOUSA et al,2017).…”
Section: Evaluation Of Biogas Production Through Anaerobic Biodigestiunclassified
“…Conhecer o grau de cristalinidade dos biomateriais é fundamental, devido a sua influência no desempenho in vivo por afetar a reabsorção e suas propriedades mecânicas. As regiões amorfas são biodegradadas e reabsorvidas mais rapidamente do que as regiões cristalinas, por não apresentarem uma ordenação espacial a longa distância (Sousa, 2016).…”
Section: Caracterizaçãounclassified